ANALISIS BERFIKIR TINGKAT TINGGI (Higher Order Thinking) DENGAN MENGGUNAKAN PETA KONSEP PADA POKOK BAHASAN LARUTAN ELEKTROLIT DAN NON ELEKTROLIT - Rahmi Hidayati; Imam Santoso; Erdawati Erdawati (Jurnal Riset Pendidikan Kimia (JRPK), 2013)
This research aims to determine the use of concept maps to develop higher order thinking skills of students. Assignment concept map performed in groups and using the software C-Map Tools. Therefore, the assessment of students 'concept maps and students' performance during the process of making a concept map. The research method used is descriptive research. Quantitative data generated from the manufacture of students' concept maps are described and analyzed to determine changes in thought processes of students in higher-order thinking. The results of this study indicate a change students' thinking processes marked with the percentage change scores on each concept map assessment kriteria, that is the determination of the relevant concepts, propositions, hierarchy, and the cross-links, so that higher-order thinking skills can be developed by assigning students create a concept map. Based on the assessment of student performance during the process of mapping concept is known that most students already have a self-management skills, teamwork, time management, respect for opinions, solving problems, and expressed the opinion that good. However, students 'skills in analyzing questions and a positive attitude toward the task is still not good. Key words: higher order thinking, concept maps, electrolyte and nonelectrolyte solutions